Metadata Retention as a Means of Combatting Terrorism and Organised Crime: A Perspective from Australia - Sarre, Rick (Asian journal of criminology, 2017)
On October 13, 2015, new laws came into force in Australia requiring telecommunications service providers to retain and store their ‘metadata’ for 2 years so that it remains available for analysis by anti-terrorism strategists and organised crime fighters. But there are ongoing issues associated with this legislative approach, including the threats to privacy thereby, and concerns that the retention system can be circumvented entirely. This paper will outline the legal and criminological questions that need to be explored in order to help policymakers work through these issues so that an appropriate balance can be struck between forestalling crime and terrorism using all available electronic means, and not unduly curtailing the legitimate rights to privacy that citizens in modern democracies currently expect to enjoy.